Pemanfaatan Minyak Jelantah Menjadi Lilin Aromaterapi sebagai Upaya Pengelolaan Limbah dan Pemberdayaan Ekonomi Masyarakat - Zuhro, Nurul Shofiatin; Azhari, Muhammad Asshiddiqi; Rovidhoh, Ana; Petrik, Shela; Izzatadiini, Arini; Cahyono, Moch. Rizki Nur Hidayat; Rachmatullah, Alya Zahirah; Labibah, Sajiya; Azizzah, Sabrina Ghina; Lestari, Cica Aisyah; Agustin, Syifa Frida (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
Used cooking oil is a household waste that may pollute the environment and harm human health if disposed of or reused improperly. This community service program aimed to provide a waste management solution while enhancing the community’s economic skills through training on producing aromatherapy candles from used cooking oil. The implementation method included awareness sessions on the hazards of used cooking oil, technical training using a learning by doing approach, and assistance in production and marketing. A total of 30 participants from the Family Welfare Movement (PKK) took part in the program. The results indicated improved knowledge and skills, the production of approximately 50 aromatherapy candles with lavender, rose, and vanilla scents, and the establishment of a community group committed to continuing independent production. The program contributed positively to the environment by reducing around 15 liters of waste oil per month and created new entrepreneurial opportunities for residents. Therefore, this initiative can serve as a sustainable community empowerment model based on circular economy principles.